Extra-skeletal plasmablastic myeloma presenting as palatal growth – An unusual entity. (2017) - Kumar, Sanjay; Bhutani, Namita; Bhargawa, Shilpi; Kataria, Sant Parkash; Sen, Rajeev
Highlights: A case of extraskeletal plasmablastic myeloma presenting as a growth of hard palate is rare. Its occurrence in young female patient is an extreme rarity and to the best of our knowledge, has never been reported in literature. A multidisciplinary approach is required for the optimal diagnosis and management of extramedullary plasmacytoma. Abstract: Introduction: Multiple myeloma (MM) is characterized by malignant proliferation of plasma cells, monoclonal bone marrow plasmacytosis, the presence of M-protein in serum and/or in urine and osteolytic bone lesions. Presentation of case: We report a case of a 28-years old female, who was diagnosed to have relapsing extra-skeletal and extra-nodal plasmablastic myeloma, an atypical variant of MM with a poor prognosis. In addition to bone marrow plasmacytosis and the presence of M protein in the serum, the patient had an extramedullary lesion affecting the hard palate. Discussion: There is a strong correlation with age. The peak incidence is seen in 6th-7th decade. The clinical course in adolescents and young individuals is generally indolent and the survival is longer. Extramedullary myelomas are rare tumors accounting for 0.4% of all head and neck malignancies. Conclusion: A case of extraskeletal plasmablastic myeloma presenting as a hard palate growth and that too in young female patient is an extremely rare and requires a multidisciplinary approach for management.